1996
DOI: 10.1021/cm950109j
|View full text |Cite
|
Sign up to set email alerts
|

Sol−Gel Synthesis of Nanocrystalline Magnesium Fluoride:  Its Use in the Preparation of MgF2 Films and MgF2−SiO2 Composites

Abstract: Thin, protective films of nanocrystalline MgF 2 were formed by spin-coating a sol that contained nanocrystalline MgF 2 , which was formed by the action of HF on a sol prepared from methanolic H 2 O 2 and Mg(OCH 3 ) 2 . These thin films on Si(100) lost fluoride to form MgO when heated at 550 °C. When the films on two such substrates were placed together face to face and heated at 550 °C, rough, abrasion resistant MgF 2 films were obtained. To form composites, nanocrystalline MgF 2 sols were mixed with silicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 20 publications
0
32
0
Order By: Relevance
“…It has been used mainly therefore as a catalyst support rather than as an acid catalyst [24,25]. Although MgF 2 of small particle size has been prepared using aqueous or aqueous-organic solgel [26] or microwave [27] techniques, the properties of the solids will be rather different than those reported in the present work, where non-aqueous sol-gel conditions have been used for syntheses of the precursors [14]. Crystalline MgF 2 is a useful host for a range of metal trifluorides, M'F 3 , providing the size of the M' cation is not too different from that of Mg 2+ [17].…”
Section: The Lewis Acidity Of Hs-alf 3 and Hs-mgfmentioning
confidence: 99%
“…It has been used mainly therefore as a catalyst support rather than as an acid catalyst [24,25]. Although MgF 2 of small particle size has been prepared using aqueous or aqueous-organic solgel [26] or microwave [27] techniques, the properties of the solids will be rather different than those reported in the present work, where non-aqueous sol-gel conditions have been used for syntheses of the precursors [14]. Crystalline MgF 2 is a useful host for a range of metal trifluorides, M'F 3 , providing the size of the M' cation is not too different from that of Mg 2+ [17].…”
Section: The Lewis Acidity Of Hs-alf 3 and Hs-mgfmentioning
confidence: 99%
“…One of the first works reported about MgF 2 NCs and SiO 2 -MgF 2 materials prepared by SG as bulk and thin films dates back to 1996 [20]. Mg(OCH 3 ) 2 and HF were used as Mg and F sources, respectively, to obtain MgF 2 sol.…”
Section: Introductionmentioning
confidence: 99%
“…It is an insulator with a broad band gap. Magnesium fluoride is used extensively in optical thin films [19][20][21][22][23], for example, as anti-reflective coatings on glasses and as rutile seed for pigment applications [24] and for composite optical filters with titania [25]. It was also reported that magnesium fluoride, which played the role of a support for a number of oxide [26,27], metallic [28] and sulfide [29] phases, enabled syntheses of catalysts active for such reactions as decomposition and reduction of nitrogen oxides [30], hydrodechlorination of chlorofluorocarbons (CFC) [31] and hydrodesulfurization of thiophene [32,33].…”
Section: Introductionmentioning
confidence: 99%